2009
DOI: 10.1149/1.3148222
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Durable PEMFC Startup Process by Applying a Dummy Load

Abstract: Various polymer electrolyte membrane fuel cell (PEMFC) startup procedures were tested to explore possible techniques for reducing performance decay and improving durability during repeated startup–shutdown cycles. The effects of applying a dummy load, which prevents cell reversal by consuming the air at the cathode, on the degradation of a membrane electrode assembly were investigated via single-cell experiments. Electrochemical techniques, including measurement of polarization curves, electrochemical impedanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 13 publications
1
27
0
Order By: Relevance
“…As shown in several operating parameters [33][34][35][36][37][38][39] that can have an impact on the degradation rate of PEMFCs under startup and shutdown cycles, including cathode humidity [37,38], cell temperature [33], application of a dummy load [35,36], and gas supply sequences [34]. The hydrogen/air interface during the startup and shutdown processes was mimicked by purging the anode and cathode channels with air after continuous air and hydrogen were supplied.…”
Section: Accelerated Lifetime Tests Under Startup-shutdown Cyclesmentioning
confidence: 99%
See 2 more Smart Citations
“…As shown in several operating parameters [33][34][35][36][37][38][39] that can have an impact on the degradation rate of PEMFCs under startup and shutdown cycles, including cathode humidity [37,38], cell temperature [33], application of a dummy load [35,36], and gas supply sequences [34]. The hydrogen/air interface during the startup and shutdown processes was mimicked by purging the anode and cathode channels with air after continuous air and hydrogen were supplied.…”
Section: Accelerated Lifetime Tests Under Startup-shutdown Cyclesmentioning
confidence: 99%
“…After the start/stop cycles, the relative number of particles with a diameter ≤2.5 nm declined from 57.20% in a fresh MEA to 1.92%. Cho et al combined the results of cross-sectional SEM and TEM to evaluate Pt/C degradation [33,34,36,38,39,45,59].…”
Section: Agglomeration And/or Dissolution Of Pt Particlesmentioning
confidence: 99%
See 1 more Smart Citation
“…In comparison, the voltage of the closed cell decreased from 0.833 to 0.801 V, and the degradation rate was 0.0213 mV per cycle, almost two It is apparent that the cell performance decreased more seriously at high current density. The performance decay in the high current density region may be ascribed to the increased contact resistance at the CCM/GDL interfaces induced by carbon oxidation during the startup and shutdown cycles, resulting in worsening of the hydrosphere transport and mass diffusion [10][11][12]. By comparison of the degradation behaviors for open-ended and closed cells, it can be concluded that the performance decay of a closed fuel cell is less serious than that of an open-ended fuel cell while operating in frequent startup and shutdown cycles.…”
Section: Polarization Curvesmentioning
confidence: 99%
“…The group of the Fuel Cell Research Center at the Korea Institute of Science and Technology has been developing several methods to improve the durability of PEMFCs [10][11][12]. Kim et al [10] investigated the effects of applying a dummy load on the degradation of a single cell. Their results suggested that applying a dummy load in starting up PEMFCs was an effective way to mitigate performance degradation.…”
Section: Introductionmentioning
confidence: 99%